Right ventricular strain impairment due to hypoxia in patients with COPD: a post hoc analysis of two randomised controlled trials - Konrad E Bloch; Mona Lichtblau; Silvia Ulrich; Felix C Tanner; Talant Sooronbaev; Maamed Mademilov; Michael Furian; Helga Preiss; Laura Mayer; Simon Rafael Schneider; Julian Müller; Stephanie Saxer; et al. (Open Heart)
Background Hypoxic pulmonary vasoconstriction leads to an increase in pulmonary artery pressure (PAP) and potentially right heart failure in healthy individuals and patients with respiratory diseases. Previous studies in patients with chronic obstructive pulmonary disease (COPD) exposed to hypobaric hypoxia have shown an increase in PAP, while traditional echocardiographic parameters revealed only minimal changes at high altitude. Speckle-tracking-derived analysis is potentially more sensitive to assess right ventricular (RV) function and we used this method to investigate the impact on RV function of patients with COPD ascending to high altitude and compared the results with the traditional echocardiographic parameters.Methods This post hoc analysis evaluates echocardiographic RV free wall strain (RVFWS) in patients with COPD GOLD grade 1–3 travelling from 760 m to 3100 m for a 2-day stay. An RVFWS over −20% was considered as an indicator of RV dysfunction.Results A total of 54 patients (57% men, mean±SD age 58±9 years, forced expiratory volume in 1 s (FEV1 % predicted 77.3±22.5)) with echocardiographs of sufficient quality were included. The mean RVFWS worsened significantly from −26.0±4.9% at 760 m to −23.9±5.4% at 3100 m (p=0.02). The number of patients with relevant RV dysfunction based on RVFWS increased from 7.4% at 760 m to 25.9% at 3100 m (p=0.02), whereas the prevalence of RV dysfunction assessed by traditional indices remained unchanged.Conclusion Exposure to hypoxia led to RVFWS impairment in more than one quarter of patients with COPD. Strain analysis is a promising, non-invasive method for evaluating RV dysfunction, even in subclinical cases and might be prognostically relevant in patients with lung diseases.Trial registration numbers NCT02450968 and NCT03173508.